Effective conservation measures to mitigate the impact of human disturbances on the endangered Egyptian vulture. (26th February 2014) - Zuberogoitia, I.; Zabala, J.; Martínez, J. E.; González‐Oreja, J. A.; López‐López, P.
Abstract A consistent body of literature suggests that migratory species, ecological specialists and/or populations living on the borders of their distribution ranges are expected to be among the most seriously affected by alterations in environmental conditions. In this framework, we tested the combined effects of human disturbance and weather conditions on the breeding performance of a long‐lived endangered scavenger, the Egyptian vulture, in a study area (Biscay, northern Spain) located close to the edge of its worldwide range. Furthermore, we tested the effect of specific management strategies aimed at preventing the impact of human disturbance on the species' breeding output. Our results showed that the breeding success was negatively correlated with weather conditions, mainly rainfall and number of rainy days in June, that is the rearing period of small nestlings. Importantly, human disturbance was the main factor affecting Egyptian vultures' productivity. In fact, during the study period (2000–2012), we detected cases of high‐level disturbance in 59 nests (30.9%) within 17 of the 22 monitored territories, which only produced three fledglings overall. In 2010, we started the application of management actions for preventing human disturbance, first in a few control territories and later, in 2011 and 2012, across the whole study area. The measures were found to be successful, as the breeding success increased to levels similar to those previously detected in non‐disturbed nests. Our results showed that management strategies aimed at preventing human disturbance are of paramount importance in order to assure the conservation of this endangered species.